2021
DOI: 10.1155/2021/6693224
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Corrosion and Fatigue on the Bending Performances of Damaged Concrete Beams

Abstract: The durability of in-service reinforced concrete bridges will be greatly reduced under the action of corrosion and the repeated load such as vehicles. In this paper, six reinforced concrete beams were cast and subjected to sustained load test for one year, and then, the alternating test of corrosion and fatigue load were carried out with the damaged concrete beams. The long-term deflection, fatigue lifetime, failure modes, and crack growth were investigated under different corrosion and fatigue working conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The publications in this field mainly cover the issues of load capacity of reinforced concrete structural members under bending. In addition to the works discussed above, the studies of Li et al [17] and He et al [18] should be noted as it devoted to the bearing capacity of reinforced concrete beams subject to corrosion. Thus, the assessment of the resistance of compressed members is a complex problem, which includes the influence of the second order effects, changes in stiffness and force eccentricity over time due to the accumulation of corrosion damage.…”
Section: Introductionmentioning
confidence: 99%
“…The publications in this field mainly cover the issues of load capacity of reinforced concrete structural members under bending. In addition to the works discussed above, the studies of Li et al [17] and He et al [18] should be noted as it devoted to the bearing capacity of reinforced concrete beams subject to corrosion. Thus, the assessment of the resistance of compressed members is a complex problem, which includes the influence of the second order effects, changes in stiffness and force eccentricity over time due to the accumulation of corrosion damage.…”
Section: Introductionmentioning
confidence: 99%
“…An important issue investigated by the authors is the reliability and durability of corrosion-damaged structures. For example, 2 of 17 in [4], an aspect of this problem is considered under cyclic loading that causes fatigue failure. It is found that corrosion is the cause of acceleration and development of fatigue cracks.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, national and foreign scientists study bearing capacity of corroded elements under dynamic multivariant loads [1][2][3], modeling of corrosion propagation [4][5], the effects from loss of bond between reinforcement and concrete are studied [6][7]. Special attention is paid to corrosion of reinforcement and [8][9] and to the phenomena of pressure of corrosion products on concrete which accompany this process, as well as to corrosion of concrete separately and its influence on the bearing capacity of elements [10]. However, insufficient attention is paid to the deformability of corroded elements.…”
Section: Introductionmentioning
confidence: 99%